2023
DOI: 10.1126/scitranslmed.abn0441
|View full text |Cite
|
Sign up to set email alerts
|

Precision functional MRI mapping reveals distinct connectivity patterns for depression associated with traumatic brain injury

Abstract: Depression associated with traumatic brain injury (TBI) is believed to be clinically distinct from primary major depressive disorder (MDD) and may be less responsive to conventional treatments. Brain connectivity differences between the dorsal attention network (DAN), default mode network (DMN), and subgenual cingulate have been implicated in TBI and MDD. To characterize these distinctions, we applied precision functional mapping of brain network connectivity to resting-state functional magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The results of neuroimaging studies demonstrated that in relatively young veterans with mild TBI, the finding of Deep white matter hyperintensities (DWMH) has a different and negative impact on memory performance than the impact of PTSD symptoms [24][25][26]. The present study did not use neuroimaging data due to the heterogeneity of the technical features of diagnostic devices and the unstructured nature of general imaging descriptions.…”
Section: Resultsmentioning
confidence: 93%
“…The results of neuroimaging studies demonstrated that in relatively young veterans with mild TBI, the finding of Deep white matter hyperintensities (DWMH) has a different and negative impact on memory performance than the impact of PTSD symptoms [24][25][26]. The present study did not use neuroimaging data due to the heterogeneity of the technical features of diagnostic devices and the unstructured nature of general imaging descriptions.…”
Section: Resultsmentioning
confidence: 93%
“…To further assess speci city and demonstrate concordance across methods, we used our lesion-based circuit as a weighted seed to assess within-network rsFC, as in our prior work 33,34 . Increased rsFC in this circuit was associated with reduced PTSD prevalence, whether controlling for depression (t=2.60, p=0.01) (Fig.…”
Section: Generalizability To Patients Without Brain Lesionsmentioning
confidence: 99%
“…Of note, the above analyses were designed to test for signi cance of the overall network, as in our prior work on localizing TMS targets near the cortical surface for psychiatric disorders 16,30,33,63,64 . Some studies have also used LNM to map symptoms to individual brain regions rather than an entire network.…”
Section: Statistical Validationmentioning
confidence: 99%
“…Relatedly, analysis of rsFC at the network level has been suggested to be more important in TBI patients where injury may have further increased the inter-individual variability already observed across healthy brains ( Gordon et al, 2017 ). Several studies have shown that focusing on rsfMRI subnetworks associated with complex symptoms reported across TBI patients may be the best way to tackle the challenge of interindividual variability ( Herrold et al, 2020 , Siddiqi et al, 2020 , Siddiqi et al, 2023 , Sultana et al, 2023 ). For example, the cingulo-opercular network and the dorsal attention network can be differentially targeted within the dorsolateral prefrontal cortex to address distinct clusters of cognitive deficits or mood problems.…”
Section: Part 3: Future Directionsmentioning
confidence: 99%